2018
DOI: 10.1007/s10126-018-9804-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Study of Immune Responses of New Zealand Greenshell™ Mussels (Perna canaliculus) Infected with Pathogenic Vibrio sp.

Abstract: Vibrio coralliilyticus is a bacterial pathogen which can affect a range of marine organisms, such as corals, fish and shellfish, with sometimes devastating consequences. However, little is known about the mechanisms involved in the host-pathogen interaction, especially within molluscan models. We applied gas chromatography-mass spectrometry (GC-MS)-based metabolomics to characterize the physiological responses in haemolymph of New Zealand Greenshell™ mussels (Perna canaliculus) injected with Vibrio sp. DO1 (V.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 91 publications
3
26
0
Order By: Relevance
“…To analyze the tissue distribution of TcMyD88, the following tissues were collected from six healthy adult T. crocea: siphonal mantle, pedal mantle, inner mantle, byssus gland, pedis, heart, gill and hemocytes. For analysis of the developmental expression patterns of TcMyD88, samples of 0, 0.5, 1,4,12,16,24,48,72,96, and 120 h-developing embryos were also obtained.…”
Section: Animals Tissue Embryonic Development Collection and Challementioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the tissue distribution of TcMyD88, the following tissues were collected from six healthy adult T. crocea: siphonal mantle, pedal mantle, inner mantle, byssus gland, pedis, heart, gill and hemocytes. For analysis of the developmental expression patterns of TcMyD88, samples of 0, 0.5, 1,4,12,16,24,48,72,96, and 120 h-developing embryos were also obtained.…”
Section: Animals Tissue Embryonic Development Collection and Challementioning
confidence: 99%
“…It has been reported that gross pathological changes to the velum and cilia occurred in diseased Crassostrea gigas larvae [15]. Moreover, V. coralliilyticus has also been associated with outbreaks of vibriosis in several other bivalve species, including Eastern oysters (Crassostrea virginica), the European flat oyster (Ostrea edulis), the great scallop (Pecten maximus), the Atlantic bay scallop (Argopecten irradians) and New Zealand green-lipped mussels (Perna canaliculus) [16,17]. Consequently, V. coralliilyticus is a significant pathogen for bivalves, contributing to dramatic losses in mollusks worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography coupled with mass spectrometry (GC/MS) is a well-established analytical method that can provide a comprehensive and systematic understanding of all metabolites in biological samples (Tsugawa et al, 2011;Nguyen & Alfaro, 2019a). GC/MS-based metabolomics has been widely applied to study the physiological responses of aquatic organisms to environmental stressors, including pathogen infection, water contaminants and aerial exposure, and many metabolites and associated pathways have been successfully identified (Guo et al, 2014;Ji et al, 2016;Chen et al, 2015;Nguyen et al, 2018aNguyen et al, , 2018c, Alfaro, Nguyen & Mellow, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…coralliilyticus/neptunius-like isolate induced perturbations of the immune system, oxidative stress, inflammation and metabolic changes at 6 days p.i. [34]. Overall, these findings provide a further insight into the pathogenic effects of V. coralliilyticus in mussels.…”
Section: Coralliilyticus Possess Several Virulence Mechanisms Incmentioning
confidence: 58%